Four in every ten infants in Northwest Ethiopia exposed to sub-optimal breastfeeding practice. - Workineh Shume Hailu; Mulat Tirfie Bayih; Netsanet Fentahun Babble (PLoS ONE, 2020)
Background Improper breastfeeding practices significantly impair the health, development, and survival of infants, children, and mothers. A Breastfeeding Performance Index (BPI) is a composite index to describe overall maternal breastfeeding practice with infants under six months of age. To date, there is insufficient evidence on breastfeeding performance index and its associated factors in Ethiopia. Objective To assess the breastfeeding performance index and its associated factors in Sekela District, Northwest Ethiopia, 2019. Methods A community-based cross-sectional study was conducted on 605 randomly selected mothers having infants aged 6 to 12 months from April 02, 2019 to May 13, 2019. Data was collected using a structured interviewer-administered questionnaire. Multivariable logistic regressions were used to identify independent predictors of BPI. Results Two hundred forty-six (40.7%) of mothers had low BPI scores. Mothers who lived alone (AOR = 3.18; 95%CI: 1.15, 8.82), mothers who were merchants (AOR = 2.75; 95%CI:1.05, 7.15), attended three antenatal care (ANC) visits (AOR = 0.42; 95% CI: 0.20, 0.82), attended four antenatal care visits (AOR = 0.35; 95%CI: 0.12, 0.82), received postnatal care (PNC) (AOR = 0.35; 95%CI: 0.19, 0.64), had poor knowledge on breastfeeding (AOR = 3.19;95%CI: 1.14, 8.89) or negative attitudes towards breastfeeding (AOR = 2.70;95%CI: 1.13, 6.45), were independent predictors of low BPI scores. Conclusions The prevalence of sub-optimal breastfeeding practice in northwest Ethiopia was very high. A mother living alone, maternal occupation, ANC visits, PNC, maternal breastfeeding knowledge, and attitude towards breastfeeding were independent predictors of low BPI scores. Nutrition promotion should be implemented by considering the above significant factors to decrease inappropriate breastfeeding practice in Northwest Ethiopia.